MEAN-VARIANCE INVESTMENT PORTFOLIO OPTIMIZATION MODEL WITHOUT RISK-FREE ASSETS IN JII70 SHARE - Shindi Adha Gusliana; Yasir Salih (International Journal of Business, Economics, and Social Development, 2022)
In investing, investors will try to limit all the risks in managing their investments. Investor strategies to minimize investment risk are diversification by forming investment portfolios, one of which is the Mean-Variance without risk-free assets. The calculation results will show the composition of the optimum portfolio return for each stock that forms the portfolio. Optimum portfolio obtained with wT = (0.39853, 0.25519, 0.13644, 0.09788, 0.11196) sequential weight composition for TLKM, KLBF, INCO, HRUM, and FILM stocks. The composition of this optimal portfolio return is ???? 0.04 with a return of 0.00209 and a portfolio variance of 0.00015. The formation of this portfolio optimization model is expected to be additional literature in optimizing the investment portfolio with the Mean-Variance.